2005
DOI: 10.1080/02650487.2005.11072926
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the research base for the policy debate over the effects of food advertising to children

Abstract: Assessing the research base for the policy debate over the effects of food advertising to children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 21 publications
1
50
0
3
Order By: Relevance
“…There is a small amount of empirical research assessing interventions in terms skills in identifying persuasive techniques (Hobbs and Frost 2003). This is primarily experimental or observational and is thus somewhat problematic in terms of validity and reliability (Livingstone 2005). Additionally, it does not provide any insights into long-term attitudinal or behavioral change that might have occurred as the result of the programs.…”
Section: Commercially-sponsored Media Literacy Interventions: Availabmentioning
confidence: 99%
“…There is a small amount of empirical research assessing interventions in terms skills in identifying persuasive techniques (Hobbs and Frost 2003). This is primarily experimental or observational and is thus somewhat problematic in terms of validity and reliability (Livingstone 2005). Additionally, it does not provide any insights into long-term attitudinal or behavioral change that might have occurred as the result of the programs.…”
Section: Commercially-sponsored Media Literacy Interventions: Availabmentioning
confidence: 99%
“…As reported above, the majority of these studies examined the acute, short-term effects of marketing on children's food behaviours (3-12 years). Many utilised between-subject study designs with children randomised to conditions (n = 63 -1302) [56,[60][61][62][66][67][68][69][70][71][72][73][74][75][76][77]; the remainder within-subject, counterbalanced designs with randomisation to condition order with a washout-period of more than two weeks (n=42-281) [ As previously mentioned, conducting experimental studies in this domain over longer periods is methodologically challenging and expensive [39] and, as such, research of this nature is limited. Two studies, however, give insight to the longer effects of food advertising exposure.…”
Section: Experimental Studies Using Premium Offersmentioning
confidence: 99%
“…Conducting experimental studies with high ecological validity in this field of research is also difficult. Given the prolific and integrated exposure to food marketing in everyday life, isolating its effect in an experimental setting is challenging and, in the longer-term, expensive and methodologically difficult [39]. The 'Bradford Hill Criteria', first published over fifty years ago, are a recognized and widelyused framework against which epidemiological studies may be examined to consider whether a causal interpretation of an observed association is valid [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…There has also been extensive work demonstrating that breakfast cereals marketed to children are more likely to be HFSS (21,24) . Assessment of other children's products has been performed in countries such as the USA, Canada and Australia, but little research has been undertaken in Europe (14,18,23,25,26) . Existing studies evaluating the differences between children's products and non-children's products have either included baby and toddler foods only or have been limited to small sample sizes (13,27) .…”
mentioning
confidence: 99%